2021
DOI: 10.5802/crmath.154
|View full text |Cite
|
Sign up to set email alerts
|

Quasihyperbolic mappings in length metric spaces

Abstract: In this paper, we discuss the local properties of quasihyperbolic mappings in metric spaces, which are related to an open problem raised by Huang et al in 2016. Our result is a partial solution to this problem, which is also a generalization of the corresponding result obtained by Huang et al in 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…We investigate new characterizations of ∂-biLipschitz mappings between domains (open and connected nonempty subsets) in quasiconvex metric spaces. For more investigations concerning properties of quasiconformal mappings in this setting, one may refer [8][9][10]20].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigate new characterizations of ∂-biLipschitz mappings between domains (open and connected nonempty subsets) in quasiconvex metric spaces. For more investigations concerning properties of quasiconformal mappings in this setting, one may refer [8][9][10]20].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The class of locally biLipschitz mappings mentioned in Theorem 1.4(4) was introduced by Bonk et al [1], where they demonstrated that there is a oneto-one correspondence between Gromov hyperbolic space category with biLipschitz mappings as morphisms and uniform space category with quasisimilarity mappings as morphisms. For more investigations about these mappings, see [18,20].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The authors answered the problem under certain additional conditions. Our result, Theorem 1.1, in this paper shows that the related conditions in [4,8,9] cannot be removed.…”
mentioning
confidence: 82%
“…Added information. After the acceptance of this paper, we found three related references, see [4,8,9]. The main aim of these papers is to investiage Väisälä's open problem discussed in this paper.…”
mentioning
confidence: 95%